IMPLIKASI AKREDITASI PERPUSTAKAAN PADA MINAT BACA SISWA SEKOLAH MENENGAH SWASTA DI KOTA SURABAYA - Dian Kristyanto; Yanuastrid Shintawati; Bakhtiyar Bakhtiyar; Rosida Syaukat; Savina Ayu Fitria (Universitas Islam Negeri Salatiga, 2026)
School library accreditation is used to recognize library standardization formally and focuses on fostering students' interest in reading by optimizing library quality. This study aims to describe the implications of library accreditation on students' interest in reading, especially in secondary schools in Surabaya City. The method used is qualitative with a multi-site design. The informant determination technique uses purposive sampling, and data analysis is carried out by gathering data, memoing, coding, profound analysis, and developing concept models. The study's results indicate that the implications of library accreditation on reading interest in schools show the involvement of human resources and library collections. Human resources emphasize cooperation, initiative, and strengthening reading interest, while the collection section focuses on policies, availability, and collection development. Research recommendations encourage schools to actively transform libraries and optimize collaboration between teachers and librarians to be active in fostering students' interest in reading Keywords: library accreditation; reading interest; educational units; implication